A Text Messaging Intervention to Increase Engagement and Retention of Men in a Community-Based Father Involvement Program. Issue 2 (3rd April 2021) - Hayward, R. Anna; McKillop, Alexander Jack; Lee, Seung Ju; Hammock, Amy C.; Hong, Houlin; Hou, Wei
Abstract: Cell phone technology is increasingly used in health and social work services for information delivery, engagement, and retention in research protocols. In this study, we explored the use of text messaging to increase engagement, participation, and retention in a responsible fatherhood program. In this mixed-methods study, men who enrolled in the program over a one year period ( N = 212) were randomly assigned to receive an intervention consisting of twice-weekly messages for 12 weeks. This study employed a concurrent nested mixed methods design with a main quantitative experimental methodology and a supplemental qualitative methodology. Measures of program engagement and participation were collected at 6- and 12-weeks post-enrollment, as well as overall retention in both the fatherhood program and the research protocol. Qualitative interviews with a sub-sample of study participants were conducted after 6 weeks of services. No statistically significant differences were found in the quantitative portion of the study across randomized groups but participants reported positive experiences with the intervention in both program feedback and qualitative interviews. Text messaging may be a low-cost, viable mechanism for engaging fathers in interventions, but further research is needed to determine the impact on program outcomes.